Stability Analysis and Design of Rock Support for Tunnel and cavern of Kathmandu University Geo-lab - Khadka, Shyam Sundar; Maskey, Ramesh Kumar (Kathmandu University Journal of Science Engineering and Technology, 2018)
This study focuses on the design and stability analysis of underground structures in the Lesser Himalayan Region of Nepal. The rock support design for such opening depends upon the rock mass strength. In this study a proposed Kathmandu University Geo-Lab tunnel and cavern, which passes through weak rock mass conditions, was used as a case study. Existing empirical and analytical methods for the stability of the proposed tunnel and cavern are used for the estimation of support pressure and design support. A detailed numerical study was carried out in 2D finite element analysis to design the tunnel in such region. The results of analysis showed that the support pressure and deformation can be predicted very well from the numerical analysis.